Underground muography with portable gaseous detectors. Issue 1 (1st November 2022) - Hamar, G; Surányi, G; Varga, D; Nyitrai, G; Oláh, L; Gera, Á; Balogh, Sz J; Barnaföldi, G G
Abstract : Muography is a novel imaging technology based on particle physics instrumentation to reveal density structure of hill-sized objects. The cosmic muon flux is attenuated while penetrating into the ground, thus the differential local flux correlates with the overburden density-length. Underground muography exploits the close-to-zenith flux, while main challenges became portability, low power consumption, and robustness against the out-of-the-laboratory environment. Various fields could benefit from this non-invasive imaging, eg. speleology, mining, archeology, or industry. Portable gaseous tracking detector systems have been designed, built, and successfully used in several underground locations. This paper presents the designed portable muography systems, the main requirements, and measurement campaigns for calibration, natural caves, and cultural heritage.